The genotype distribution of hepatitis C in southeastern Taiwan: Clinical characteristics, racial difference, and therapeutic response. Issue 11 (6th November 2015) - Cheng, Chun‐Han; Chen, Huan‐Lin; Lin, I‐Tsung; Wu, Chia‐Hsien; Lee, Yuan‐Kai; Wong, Ming‐Wun; Bair, Ming‐Jong
Abstract: The genotypes of hepatitis C virus (HCV) are associated with the therapeutic response. The racial diversity of Taitung, Taiwan is heterogeneous and a distinguishing feature; how such racial differences influence the genotype distribution and treatment outcome has not been well studied. The objective of this study is to elucidate the HCV genotype distribution in southeastern Taiwan and to analyze the racial differences influencing genotypes and clinical implications. In this retrospective cohort study, we included 343 patients who had been treated with peginterferon‐alpha plus ribavirin. The predominant HCV genotype in the southeastern area was type 1 (43.7%), followed by type 2 (37.0%). The proportion of patients mixed with genotype 1 was lower in indigenous vis‐à‐vis nonindigenous groups (46.1% and 60.2%, p = 0.02). The prevalence of genotype 6 (5.2%) seems higher than in the general population of Taiwan and showed no difference between indigenous and nonindigenous people. The sustained virological response rate was higher in patients without genotype 1, low baseline HCV RNA (≤ 400, 000 IU/mL), and in patients who achieved rapid virological response. Racial differences did not influence the therapeutic response. In this retrospective study, the proportion of HCV genotype 6 appeared slightly higher in southeastern areas than in the general population in Taiwan. The prevalence of genotype 1 in indigenous people was statistically lower than in nonindigenous people. Sustained virological response rate did not show any significant difference between indigenous and nonindigenous people in the current study.